Korean Waves Popularity on Korean Food Purchasing Decisions in Jakarta - Budi Setiawan; Baskoro Harwindito; Farah Hersa Novani Putri (International Journal of Travel, Hospitality and Events, 2024)
Purpose: The goal of this study was to ascertain whether the popularity or trend of the Korean Wave influences Korean food purchases in Jakarta. Research method: Quantitative research methodologies are being used in this study. Sources of information were gathered through observation and questionnaires, as well as primary and secondary data. The research population consisted of 83 customers at Annyeong Korean Food Café Tebet. Result and discussion: The results of observations in the R table obtained a sample value (N) = 30 of 0.3061, resulting in a value (R.Calculated) greater than R.Table. Apart from that, the purchasing decision variables (Variable Y) all produce values (R.Calculated) greater than R.Table. So, this research can be said to be valid—the reliability test results and all the variable results. The linearity test shows the Sig value. The deviation from linearity is 0.384, which is greater than 0.05. There is a linear relationship between the Korean Wave variable and the Purchasing Decision Variable. The Kolmogorov-Smirnov normality test with SPSS shows a significance value of 0.078, more significant than 0.05. So, it can be concluded that the residual values are normally distributed so that the results of this analysis can be continued for further testing. The Pearson test produced a value of 0.766, more significant than the R table value of 0.213. So, it can be concluded that there is a strong relationship between the Korean Wave variable (X) and purchasing decisions (Y) because the value on the correlation coefficient scale is 0.60 – 0.79. Implication: From the research results, theoretical implications can be put forward, and it can be concluded that there is a strong impact between the Korean wave and the purchasing decision of Korean Food.   Keywords: Popularity, Korean Wave, Purchase Decision, Korean Food